Aliphatic-aromatic poly(carbonate-co-ester)s containing biobased furan monomer: Synthesis and thermo-mechanical properties. (3rd January 2018) - Cai, Xiaodong; Yang, Xiangui; Zhang, Hua; Wang, Gongying
Abstract: Aliphatic-aromatic poly(carbonate- co -ester) random copolymers poly(butylene carbonate- co -furandicarboxylate)s (PBCFs) with different composition had been prepared from dimethyl carbonate (DMC), 1, 4-butanediol (BD) and bio-based dimethyl furan-2, 5-dicarboxylate (DMFA) by two-step melt polycondensation method. A series of characterization results can be explained as follows: the varying melting temperature ( T m ) and enthalpy ( ΔH m ) displayed that the copolymers were strongly dependent upon the compositions of butylene carbonate (BC) and butylene furandicarboxylate (BF) units. In addition, glass transition temperature ( T g ) noticeably increased with the content of BF units increasing, which agreed with Fox equation; a comparative kinetics research of isothermal crystallization of homopolymer and copolymers with different composition displayed that the existence of BF units could accelerate the crystallization rate of PBC. Furthermore, all of PBCFs exhibited a typical isodimorphic cocrystallization behavior, whose crystal lattice structure shifted from PBC type crystal to PBF type; the thermal stability of PBCFs also expressed to be enhanced during the process of the increasing BF unit content; last but not the least, the mechanical performances could be easily by adjusting the feed components. Graphical abstract: Bio-based aliphatic-aromatic poly(carbonate-co-ester) random copolymers. Image 1 Highlights: Bio-based aliphatic-aromatic poly(carbonate-co-ester) random copolymers had been synthesized via two-step melt polycondensation method. Bio-based furan units could significantly influence the thermal transition behavior, thermal stability as well as crystallinity of copolymers. The mechanical properties of copolymers can be adjusted by changing the feed composition.